2023
DOI: 10.1063/5.0144199
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wave effects on stability and performance in rotating detonation combustors

Abstract: Recently, with the development of detonation-based propulsion systems, scholars have begun to study how to perform mode control on the rotating detonation combustor (RDC). It is important to figure out the influence of operation mode transition on the RDC. Actually, the essential of different modes is the different multi-wave structures. In this study, two-dimensional numerical simulations of the RDC are conducted to study the multi-wave effect on the stability and performance of the RDC. A uniform inlet condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this part, we simulated a one-dimensional planar detonation wave with kerosene/air mixtures under a grid size of 0.1 mm. A similar validation of hydrogen/air detonation was conducted by Sheng [53] with BYCFoam, which gave a satisfactory result with a maximum relative error around 0.2%.…”
Section: One-dimensional Planar Detonation Wavementioning
confidence: 79%
See 1 more Smart Citation
“…In this part, we simulated a one-dimensional planar detonation wave with kerosene/air mixtures under a grid size of 0.1 mm. A similar validation of hydrogen/air detonation was conducted by Sheng [53] with BYCFoam, which gave a satisfactory result with a maximum relative error around 0.2%.…”
Section: One-dimensional Planar Detonation Wavementioning
confidence: 79%
“…BYCFoam and its early version BYRFoam have been widely used in the RDC simulations of our group [25][26][27][28]53]. In this part, we performed a two-dimensional test to assess the computational efficiency improved by the AMR and DLB algorithms.…”
Section: Two-dimensional Rotating Detonation Combustormentioning
confidence: 99%
“…These results suggest that the detonation wave propagation in case 4 with RHFI is more stable when compared to case 3 with SFI. Additionally, these consequences can be further understood through the study of Sheng et al [44]. In their study, they concluded the following.…”
Section: Detonation Propagation Modesmentioning
confidence: 96%
“…The circular nozzle is more active in the spreading of the fuel in the combustor and the use of an internal air jet effectively increases fuel in a combustor of the scramjet. Keywords Combustion chamber, Fuel jet, Non-equal jets, Supersonic flow Advance in spacecraft and high-speed vehicles has been required for the access to the far distance in space for explorations [1][2][3] . Thus, different aspects and segments of spacecraft has been investigated by researchers to control and improve the efficiency of this vehicles in far distance 4,5 .…”
Section: Influence Of the Non-equal Aligned Nozzles For Fuel Injectio...mentioning
confidence: 99%